Sex differences in behavioral and neural responses induced by witnessing social defeat stress during adolescence or adulthood in mice - Canto-de-Souza, Lucas [UNESP]; Baptista-de-Souza, Daniela [UNESP]; Thiele, Mariana [UNESP]; Garcia, Vitor Gonçalves [UNESP]; Silva, Katellyn Costa [UNESP]; de Souza, Fernanda Victorino [UNESP]; Crestani, Carlos C. [UNESP]; Nunes-de-Souza, Ricardo Luiz [UNESP] (Elsevier, 2025)
Psychosocial stress can lead to emotional disorders and memory-related cognitive impairments. Evidence suggests that stress effects vary with age and sex, involving brain structures such as the medial prefrontal cortex (mPFC), amygdala, and hippocampus. This study hypothesized that witnessing social defeat stress (WSDS) during adolescence or adulthood would produce anxiety- and depression-like behaviors and cognitive deficits in adulthood, with outcomes affected by sex. We examined WSDS effects on male and female mice exposed during adolescence or adulthood, assessing: (i) social avoidance in the social interaction test, (ii) anxiety in the elevated plus-maze (EPM) and open field tests, (iii) cognition in the object recognition test, (iv) depression-like behaviors in the sucrose splash test, and (v) ΔFosB expression in neurons within the mPFC, basolateral amygdala (BLA) and dorsal hippocampus (DH). WSDS during adolescence resulted in reduced EPM open-arm exploration in both sexes and impaired novel object discrimination in males. In adulthood, WSDS reduced open-arm entries only in females and impaired novel object discrimination in both sexes. Female mice showed higher mPFC ΔFosB labeling than males, while control males exhibited higher labeling in the BLA and DH, which was not observed in WSDS mice. In conclusion, this study shows that WSDS during adolescence or adulthood induces anxiety-like behavior in both sexes, cognitive impairments in males, and sex-specific patterns of neuronal activation.
Keywords: Amygdala; Anxiety; Hippocampus; Medial prefrontal cortex; Short-term memory; Witnessing social defeat stress